Cognitive constraints on the structure and dynamics of social networks - Dunbar, R (2008)
Everyday social activities take place within an environment peopled by a specific set of individuals (our social network). The author reviews the evidence that our social world is both limited in size and highly structured. This structuring consists of a series of circles of acquaintanceship, the successive layers of which progressively include more individuals with whom we have less intense relationships. Although these layers have very consistent typical sizes, there is considerable individual variation because of individual differences in gender, personality, and social-cognitive abilities. The author considers some of the implications of these structural components for the way in which we organize our social lives. © 2008 American Psychological Association.